ENabling Reduction of low-Grade Inflammation in Seniors (ENRGISE) Pilot study: Concept, rationale and design - Manini, Todd M. (J Am Geriatr Soc, 2017)
BACKGROUND: Low-grade chronic inflammation, characterized by elevations in Interleukin-6 (IL-6), is an independent risk factor for impaired mobility and slow walking speed in older adults. DESIGN: The ENRGISE (ENabling Reduction of low-Grade Inflammation in SEniors) Pilot study was a multicenter, double-blinded, placebo-controlled randomized pilot trial of two interventions to reduce IL-6 levels. SETTING: Five university-based research centers. PARTICIPANTS: The target enrollment was 300 men and women aged ≥70 years who have an average plasma IL-6 >2.5 and <30 pg/ml across 2 measures, separated by at least one week. Participants had low to moderate physical function, defined as 1) self-reported difficulty walking ¼ mile or climbing a flight of stairs and 2) a usual walk speed <1 m/sec on a 4 m usual paced walk. INTERVENTION: Participants were randomized to Losartan (LO), omega-3 (ω-3) fish oil, combined LO+ω-3 or placebo. Randomization was stratified depending on eligibility for each group. A titration schedule was implemented to reach a dose that was safe and effective on IL-6 reduction. Maximal doses were 100 mg/day for LO and 2.8 g/day for ω-3 fish oil. MEASUREMENTS: IL-6, walking speed over 400 meters, physical function (Short Physical Performance Battery), other inflammatory markers, safety, tolerability, frailty domains, and maximal leg strength were measured. RESULTS: The ENRGISE Pilot Study was designed to determine recruitment yields, feasibility, medication tolerance and adherence, and to provide preliminary data to help justify a sample size for a more definitive randomized trial. CONCLUSIONS: The ENRGISE Pilot Study will inform a larger subsequent trial that is expected to have important clinical and public health implications for the growing population of older adults with low-grade chronic inflammation and mobility limitations.